2016
DOI: 10.1007/s11554-016-0574-2
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Light Speed Labeling: an efficient connected component algorithm for labeling and analysis on multi-core processors

Abstract: International audienceIn the last decade, many papers have been published to present sequential connected component labeling (CCL) algorithms. As modern processors are multi-core and tend to many cores, designing a CCL algorithm should address parallelism and multithreading. After a review of sequential CCL algorithms and a study of their variations, this paper presents the parallel version of the Light Speed Labeling for Connected Component Analysis (CCA) and compares it to our parallelized implementations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…Two datasets of black and white random noise images have been generated to stress how the behavior of algorithms varies with the percentage of foreground pixels (density) and minimum size of foreground blocks (granularity) [21]. Resolution is 2048 × 2048 for two-dimensional images, and 256 × 256 × 256 for three-dimensional volumes.…”
Section: Random Synthetic Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two datasets of black and white random noise images have been generated to stress how the behavior of algorithms varies with the percentage of foreground pixels (density) and minimum size of foreground blocks (granularity) [21]. Resolution is 2048 × 2048 for two-dimensional images, and 256 × 256 × 256 for three-dimensional volumes.…”
Section: Random Synthetic Imagesmentioning
confidence: 99%
“…In the last years, the fast advance of Graphic Processing Units (GPUs) encouraged the development of algorithms specifically designed to work in a data parallel environment. So, along with sequential solutions [16], [17], [18], [19], many novel algorithms exploiting the parallelism of both CPUs and GPUs have been proposed [20], [21], [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…The GPU-based CCL algorithms should address the data-dependent issues. Cabaret et al [39] benchmarked the existing GPU-based CCL algorithms and concluded they were all multi-pass data-independent approaches, which were not suitable for GPU acceleration. Instead of GPU programming technology, they utilized OpenMP to program a parallel version of CCL on multi-core processors.…”
Section: The Gpu-accelerated Frameworkmentioning
confidence: 99%
“…The latter has the same size of the input image and contains the labels assigned to the input pixels.Several attempts to improve the performance of these algorithms were presented in the recent past. They exploit parallelism by means of either multi-core processors and Graphics Processing Units (GPUs) [5,[27][28][29][30][31] or custom hardware architectures [10,11,[14][15][16][17][18][19][20][21][22][23]26]. As it is well known, for many consumer applications, like those related to the Internet of things (IoT), reaching high speed is as important as achieving low cost and high energy efficiency [16,32].…”
mentioning
confidence: 99%